Deformation Characteristic Analysis and Engineering Application of a Variable Cross-sectional Flexible Pin - Chen Hengjian; Xiao Shuhong (Jixie chuandong)
In this study, a variable cross-sectional flexible pin of a megawatt wind turbine gearbox is taken as the research object, and the deflection curve equation of the variable cross-sectional flexible pin considering the influence of shear deformation is established. The deflection equation and slope-deflection equation of the variable cross-sectional flexible pin are obtained by using the Green's function method. The effectiveness of this method is verified by comparing with the calculation results of the engineering algorithm and the finite element method. The simulation model of the wind power gearbox is established using Romax software, and it is verified that the deformation characteristics of the variable cross-sectional flexible pin can improve the load distribution and load sharing coefficient. The influence of the supporting stiffness of the pin and gear mesh misalignment on the load sharing performance is investigated. The research results provide a theoretical basis for improving the load sharing performance of the wind turbine gearbox and the design optimization of the variable cross-sectional flexible pin.